The Lincoln Highway : main street across America - Hokanson, Drake, 1951- (University of Iowa Press, 1999)
In his new introduction to this tenth anniversary edition, Hokanson revisits the Lincoln Highway and finds it changed - much for the better - since the original publication of this book. Most notably, he calls attention to the reinvigorated Lincoln Highway Association and its efforts to preserve what is left of the old road. Hokanson finds more and more tourists traveling the road - not only Americans but foreigners as well - by car, bus, and motorcycle on journeys not to any particular destination but simply to see America. -- Provided by publisher.